MXene/chitosan/lignosulfonate (MCL) nanocomposite for simultaneous removal of Co(II), Cr(VI), Cu(II), Ni(II) and Pb(II) heavy metals from wastewater. (6th March 2023) - Othman, Zakarya; Mackey, Hamish R; Mahmoud, Khaled A
Abstract: In this work, a novel Ti3 C2 T x MXene/chitosan/lignosulfonate adsorbent (MCL), was prepared via a facile decoration of Ti3 C2 T x MXene sheets with chitosan/lignosulfonate nanospheres as a renewable and biodegradable additive that can improve the biocompatibility and aqueous stability of MXenes. Chitosan/lignosulfonate nanospheres were stabilized on the surface of MXne sheets, endowing them with a variety of surface functionalities, high specific surface area, and antioxidant characteristics. The competitive adsorption of multi-metal systems revealed that MCL had a preferential adsorption affinity toward various heavy metal ions; the MCL removal efficiency for the quinary-metal ions adsorption followed a trend of Pb(II) > Cr(VI) ≈ Cu(II) > Ni(II) ≈ Co(II) in neutral pH conditions. A moderate reduction was observed for Cu(II) and Cr(VI) ions. For all metals, the kinetics data fitted well with the pseudo-second-order model, and the adsorption equilibrium was best described by the Langmuir model. The adsorption mechanism is suggested to be a synergic combination of electrostatic interaction, surface complexation, and ion exchange. The findings of this study provide a new approach for eco-friendly MXene surface modification and give a general pattern of metal pollutants interactions during adsorption.